2018
DOI: 10.1016/j.sleh.2017.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a physical activity accelerometer device worn on the hip and wrist against polysomnography

Abstract: PA accelerometer devices worn on either wrist provide valid estimates of TST, WASO, and SE when compared with PSG. Further studies are needed to investigate methods to improve assessment of sleep parameters by PA accelerometer devices to advance device integration and assessment 24-hour activity in populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 34 publications
0
70
1
Order By: Relevance
“…Participants wore a small, light-weight, wrist-worn triaxial accelerometer for 9 days (ActiGraph wGT3X-BT, Actigraph, LLC, Pensacola, FL, 2013) [18][19][20][21]. Prior to use, the monitors were connected to an IBMcompatible computer via USB interface and initialized to sample at 30 Hz, using proprietary software (Actilife 6.13.4, Actigraph, LLC, Pensacola, FL, 2009-2015).…”
Section: Accelerometer Data Collection and Data Reductionmentioning
confidence: 99%
“…Participants wore a small, light-weight, wrist-worn triaxial accelerometer for 9 days (ActiGraph wGT3X-BT, Actigraph, LLC, Pensacola, FL, 2013) [18][19][20][21]. Prior to use, the monitors were connected to an IBMcompatible computer via USB interface and initialized to sample at 30 Hz, using proprietary software (Actilife 6.13.4, Actigraph, LLC, Pensacola, FL, 2009-2015).…”
Section: Accelerometer Data Collection and Data Reductionmentioning
confidence: 99%
“…Actigraph GT3X accelerometers (Actigraph, Pensacola, Florida, USA) were used for sleepwake scoring for seven consecutive nights during a regular school week (76,77). The accelerometer was attached to the non-dominant wrist in order to improve compliance and also to record isolated arm movements (62,78). If at least ten consecutive minutes were categorised as awake, the sleep period ended.…”
Section: Sleep Analysismentioning
confidence: 99%
“…PSG validation studies of the ActiGraph published for both children and adults do not include WASO metrics for this device (16,24). In part this may be due to algorithms within the proprietary software for analyzing ActiGraph sleep data.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, when a person has very restless sleep, in the case of some sleep disorders, actigraphy can underestimate sleep (10). In addition, most sleep algorithms were developed for devices worn at the wrist and only a limited number of studies in adults (11)(12)(13)(14)(15)(16) have demonstrated the accuracy of these algorithms compared to PSG when worn at the hip. To our knowledge, there are no studies that compare actigraphs worn at the hip to PSG in children.…”
Section: Introductionmentioning
confidence: 99%